Colloidal Nanoplatelets: Platelet‐in‐Box Colloidal Quantum Wells: CdSe/CdS@CdS Core/Crown@Shell Heteronanoplatelets (Adv. Funct. Mater. 21/2016). (6th June 2016) - Kelestemur, Yusuf; Guzelturk, Burak; Erdem, Onur; Olutas, Murat; Gungor, Kivanc; Demir, Hilmi Volkan
Abstract : On page 3570, H. V. Demir and co‐workers synthesize CdSe/CdS@CdS core/crown@shell nanoplatelets (NPLs) with a novel 3D architecture resembling a platelet‐in‐box structure. This leads to increased photoluminescence quantum yield, enhanced absorption, and eliminated trap sites, enabling favorable excitonic properties for low‐threshold gain. Carefully heterostructured NPLs will play a critical role in building high‐performance colloidal optoelectronic devices.